Flame Spray Synthesis of VOPO4 Polymorphs - Jodhani, Gagan; Mikaeili, Fateh; Gouma, Pelagia Irene (Frontiers in Materials, 2019)
VOPO4 is a polymorphic compound that exhibits excellent catalytic and electronic properties. Here, formation of different VOPO4 polymorphs two different organic components as precursors is investigated for the first-time using flame spray pyrolysis process as an alternative method to hydrothermal synthesis of VOPO4, the only method currently known for its synthesis. Ammonium based salts of Vanadium and Phosphorous dissolved in aqueous solution were used as precursor for the process. The products from the flame spray process were found to be hollow and amorphous particles in range of 2-10µm with shell thickness in in between 200-300nm. Upon calcination and oxidation, the size of spherical particles grew in diameter and crystallization proceeded. However, the surface of calcined particles showed it was composed of smaller grains in the size range of 0.5-1µm. Finally, the size dependence stability of different polymorph of VOPO4 is discussed as well as the effect of the different precursors used to stabilize Alpha-II and Beta VOPO4 polymorphs.